2019
DOI: 10.1007/s00446-019-00349-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficient randomized test-and-set implementations

Abstract: We study randomized test-and-set (TAS) implementations from registers in the asynchronous shared memory model with n processes. We introduce the problem of group election, a natural variant of leader election, and propose a framework for the implementation of TAS objects from group election objects. We then present two group election algorithms, each yielding an efficient TAS implementation. The first implementation has expected max-step complexity O(log * k) in the location-oblivious adversary model, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Follow-up work on time upper bounds has extended these results to the adaptive setting, showing logarithmic expected step complexity in the number of participating processors k [4,16]. Further, Giakkoupis and Woelfel [16] showed that, if the adversary is oblivious to the randomness used by the algorithm, O(log k) step complexity is achievable, improving upon a previous sublogarithmic upper bound by Alistarh and Aspnes [2]. Another related line of work has focused on the space complexity of this problem, which is now resolved.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Follow-up work on time upper bounds has extended these results to the adaptive setting, showing logarithmic expected step complexity in the number of participating processors k [4,16]. Further, Giakkoupis and Woelfel [16] showed that, if the adversary is oblivious to the randomness used by the algorithm, O(log k) step complexity is achievable, improving upon a previous sublogarithmic upper bound by Alistarh and Aspnes [2]. Another related line of work has focused on the space complexity of this problem, which is now resolved.…”
Section: Introductionmentioning
confidence: 95%
“…Another related line of work has focused on the space complexity of this problem, which is now resolved. Specifically, it is known that Ω(log n) distinct registers are necessary [28,16], and a breakthrough result by Giakkoupis, Helmi, Higham, and Woelfel [15] provided the first asymptotically matching upper bound of O(log n), improving upon an O( √ n) algorithm by the same authors [14]. The clear gap in the complexity landscape for this problem concerns time complexity lower bounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation